Development of village Economic Potential through Management Laturake Village Owned Enterprise (BumDesa), Taniwel District, West Seram - Micrets Agustina Silaya; Dessy Balik; Gwenn LL Pattinama (PT FORMOSA CENDEKIA GLOBAL, 2023)
Village-Owned Enterprises, hereinafter referred to as BumDes, are business entities whose capital is wholly or substantially owned by the village through direct participation originating from separated village assets to manage assets, services and other businesses for the greatest possible welfare of the village community. BumDes management is fully carried out by the village community, namely from the village, by the village, and for the village. The program carried out by the BumDes in Laturake Village is the processing of Lawang Oil and Damar from the trees (resin trees and mace trees) owned by the community by buying them from the Bumdes and then processing them and then selling them back. This objective is to determine the development of the village's economic potential through the management of village-owned enterprises (BumDes) in Laturake Village, Taniwel District, West Seram. This research is a type of field research research and the population as well as the sample in this study are the Village Head, Head of Bumdes, BumDes Members, Village Community. Data collection techniques used are interviews and documentation. The data analysis technique used is a qualitative analysis method using inductive thinking. The results showed that the management of BumDesa in Laturake Village, Taniwel District, West Seram Regency had quite a positive impact on the Laturake village community. BumDes had made a good effort to see, observe and consider what potential could and might be developed in this Laturake village, namely by processing the roots of anise trees which have not been touched for recycling